IMPLEMENTATION OF THE AL-QURAN LITERACY ERADICATION PROGRAM FOR INMATES AT CLASS IIA BANCEUY PRISON IN BANDUNG - Baskara, Zidan Jabal Attoriq; Rifani, Denny Nazaria (Universitas Nusa Cendana, 2025)
This study aims to evaluate the Brantas Buta Baca Al-Qur'an Program at Class IIA Banceuy Bandung Penitentiary, which is designed to increase religious awareness and develop the personality of prisoners. This study uses a qualitative method with an observation approach, document study, and in-depth interviews with the Head of Binadik, Bimkemaswat staff, two mentors from prisoners, and two prisoners. The background of this study focuses on the low participation of prisoners in the coaching program, most of whom come from criminal backgrounds such as theft, corruption, narcotics, and murder, as well as minimal understanding of religion. The findings of the study indicate that this program, although supported by a strong legal basis and adequate facilities, still faces obstacles such as low participation of prisoners, limited teaching staff, and age challenges in the learning process. Nevertheless, this program has succeeded in increasing the ability to read the Qur'an and religious awareness among participating prisoners. Suggestions for increasing the effectiveness of the program include increasing prisoner motivation through socialization, adding teaching staff, and special approaches for elderly prisoners. With these steps, it is hoped that this program can be more effective in achieving its goals, namely to foster prisoners to have better personalities and be ready to return to society with a deeper understanding of religion. Keywords: Blind Reading Al-Qur'an Program; Banceuy Prison; Personality Development; Prisoners; Religious Awareness